Uncovering "Hidden Messages" in Hillary Clinton's Concession Speech Post-Presidential Defeat: A Critical Discourse Analysis - Dery Rovino (Journal of English Language and Culture, 2019)
Due to a narrative that speeches may assist with understanding gender identity indexical(s) in politics, this study aims to discover such meanings underneath the text production of Hillary Clinton’s concession speech post-defeat in the latest US presidential election. Through Critical Discourse Analysis – Text as A Critical Object (CDA – TACO), it seems evident in Hillary Clinton’s speech that there are patriotic lexical choices, parallelism, alliteration, anthropomorphization, and repetition for emphasis, personal pronoun “I” and “my”, suggesting a certain degree of assertiveness, which are generally specific to male politicians (Reyes, 2015). There is a marked use of collective pronoun “we”, “our”, connoting a level of intimacy between the speaker and audience, interestingly however, evidenced not only on Clinton’s speech but male politicians as wel, thus rendering it gender-neutral. Evidences of backgrounding, thus distancing self, when the politician utters disappointments are noticeable. Findings partially prove that gender-driven lexical choice by Hillary Clinton noticeably conforms to those of male orators in politics, although most of her expressions suggest commonality of political speeches. Limitations of the study are put forth.Keywords: gender; politics; identity indexical(s); CDA